RANCANGAN HANDOUT BIOLOGI PADA MATERI PROTISTA UNTUK SMA KELAS X - Merlin Kritstina Marbun; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of handout design in class X protista high school learning material. This research was conducted at the Binawidya Riau University in August-December 2020. The design of this handout refers to the ADDIE development model, the stage used is only the analysis and design stage. The analysis stage by analyzing the curriculum, syllabus, KD, and the material in accordance with the results of the study. The design stage is designing learning tools in the form of a syllabus and lesson plans, and designing a handout consisting of a cover, foreword, contents, study instructions, (KI, KD, and IPK), introduction, elaboration of subject matter, evaluation, and reference sources. The conclusion is the biology handout design on KD 3.6 and KD 4.6 specifically for protista topic can be used as handout teaching materials for Senior High School student Grade X.Key Words: Handout, Protista